2015
DOI: 10.5709/acp-0176-9
|View full text |Cite
|
Sign up to set email alerts
|

Executive Resources and Item-Context Binding: Exploring the Influence of Concurrent Inhibition, Updating, and Shifting Tasks on Context Memory

Abstract: Previous research has demonstrated that context memory performance decreases as a result of cognitive load. However, the role of specific executive resources availability has not been specified yet. In a dual-task experiment, participants performed three kinds of concurrent task engaging: inhibition, updating, or shifting operations. In comparison with a no-load single-task condition, a significant decrease in item and context memory was observed, regardless of the kind of executive task. When executive load c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…34 The inhibitory control may have relevance to the ability to cope with more than one task at a time. 35,36 The results of this study showed that there were moderate correlations between change in inhibitory control and change in dual-task performance (Table 4). These findings support that dual-task training has the potential to induce cognitive plasticity in older adulthood, thus preserving the efficiency of supervisory brain areas in which inhibitory control is involved and then enhancing the execution of dualtask or multitask.…”
Section: Effects Of Exergame In Older Adultsmentioning
confidence: 74%
“…34 The inhibitory control may have relevance to the ability to cope with more than one task at a time. 35,36 The results of this study showed that there were moderate correlations between change in inhibitory control and change in dual-task performance (Table 4). These findings support that dual-task training has the potential to induce cognitive plasticity in older adulthood, thus preserving the efficiency of supervisory brain areas in which inhibitory control is involved and then enhancing the execution of dualtask or multitask.…”
Section: Effects Of Exergame In Older Adultsmentioning
confidence: 74%
“…Information updating is connected with the monitoring and encoding of incoming informationit is not a passive storing but an active manipulation of the relevant information (cf. Nieznański et al, 2015).…”
Section: Studymentioning
confidence: 99%
“…In other words, participants that are fatigued are more susceptible to cognitive overload and their performance is heavily dependent on the capabilities of the central executive (in terms of the theory of working memory by Baddeley & Hitch, 1974) or controlled attention (in terms of the approach of Engle, Kane, & Tuholski, 1999). When two tasks have to be executed simultaneously or switched alternately under cognitive load, they interfere with each other, competing for general and/or specific cognitive resources (e.g., Nieznański, Obidziński, Zyskowska, & Niedziałkowska, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent work investigating the relationship between binding and executive functions has demonstrated that binding shares common resources with the executive function of inhibition (Nieznańsk, Obidziński, Zyskowska, & Niedziałkowska, 2015). When participants in our study searched for a word that embodied the three stimuli words, they were also solving a binding problem.…”
Section: Discussionmentioning
confidence: 99%